Comparison of physical and strength properties for different age group of shorea macrophylla in Sarawak - Wong, Siang Long (Universiti Malaysia Sarawak, UNIMAS, 2010)
Timber which is mostly used in construction is decreasing due to deforestation done by human being. As a result some of the construction materials are replaced by other materials such as plastic, steel and concrete. This will surely increase the cost of material indirectly increase the cost of construction. By replacing those materials like plastic, steel and concrete will increase global warning since plastic will not decompose and the source for steel and concrete are from the mining plant. Hence, to overcome this problem, fast growing timber species will be introduce. Fast growing timbers with its fast growing rate and allowed to be harvest in ten to twenty years. Therefore, this study is carried out to find the difference in strength and physical properties of 13 and 22 years of age of fast growing timber species – Shorea Macrophylla. Basic density, MOR, MOE, and compressive strength of Shorea Macrophylla with different age and condition will be investigated in order to find out the constructability of Shorea Macrophylla in construction field. From the result analyses it was notice Shorea Macrophylla in both age are categorize under softwood, and in strength group of D in Malaysia Standard of grading rules. Therefore, Shorea Macrophylla is only suitable to act as internal wall boarding in construction.